Orthopaedic Services during Nationwide COVID-19 Lockdown: Dhulikhel Hospital, Kathmandu University Hospital Experience and Review - Kayastha, S.R.; Parajuli, B.; Basi, A.; Shrestha, D. (Kathmandu University Medical Journal, 2020)
Background The Nepal government issued a nationwide lockdown due to COVID-19 from 24 March to 21 July 2020. This halted elective medical services in our hospital. A number of modifications in the orthopaedic practices at our department were made. Objective This article discusses the impact on orthopaedic load at the Department of Orthopaedics and Trauma, Dhulikhel Hospital, Kathmandu University Hospital during the lockdown. Method This is a longitudinal observational study done during the nation-wide lockdown including all the patients who presented to the hospital requiring orthopaedic consultation. For comparison purposes, the patient numbers from the same date in previous year (2019) were retrieved. Result We received no COVID-19 cases requiring orthopaedics consultation. A total of 1828 patients were seen in the Orthopaedic Outpatient Department, 1077 trauma patients in the Emergency Department, 216 patients were admitted and 210 orthopaedics procedures were performed at the operation theatre. There was 82.21% decrease in OPD patients and 56% less surgeries in OT compared to the same duration of last year. Conclusion There was a great reduction in the patient numbers visiting the hospital, which reflected in decreased number of admission and surgery. A greater part of our work during the lockdown was trauma.